A autoria na tradução artístico-poética da Língua Portuguesa para a Libras: (in)visibilidade em dimensão verbo-visual - Santos, Ricardo Ferreira (2022)
The objective is to investigate the activity of translating artistic-poetic text from Portuguese Language (LP) to Brazilian Sign Language (Libras), by describing, interpreting, and analyzing the verbal, verbal-visual, and extraverbal elements that indicate authorship in the creation of this aesthetic object. Currently, it is observed an increase of poetries being translated from LP to Libras to be shared on online websites. Because of an emergent activity linked to discursive genre (poem), a substantial change occurs in the concept of how to translate Sign Language into an audiovisual media. The research questions are: (i) in the translation of artistic-poetic materials from LP to Libras, how is authorship established? (ii) in light of the semioticideological materiality present in the texts to be translated, what evaluative and strategic perspectives do the subjects in charge of translation? (iii) in the enunciative-discursive mobilization and the process of creating new verbal-visual material in the translation task, how do deletions and insertions of other semiotic-ideological elements occur? From these questions, the hypothesis is the discursive subjects, responsible for the artistic-poetic translation work, realize semiotic-ideological visibilities and invisibilities through the process of recreation-cocreation and a body-text, and as a result, create meanings that differ from those produced in the poem. They create a new aesthetic object, a verbal-visual poetics. The study of verb-visuality, as well as the Sign Language Translators and Interpreters (ETILS), was based on the Bakhtin Circle's dialogic perspective on language. Firstly, it was chosen three artistic-poetic texts from the YouTube channel that were translated from LP to Libras: "Todas as manhãs," a poem by Conceição Evaristo, translated by Mirian Caxilé, Lívia Vilas Boas, Edinho Santos, and Nayara Rodrigues (2016); "Liberdade," a poem by Carlos Drummond de Andrade, translated by Uziel Ferreira and Grecia Catarina (2017); and "Laço de fita," a Castro Alves poem, translated by Jonas Medeiros (2016). The following criteria were used to select and delimit the corpus: (i) the audiovisual materials have some aesthetic similarities; (ii) the text of the translation into Libras is performed by certain subjects, and the audiovisual product is enunciated by another body-text (discursive subject); and (iii) the audiovisual product is produced and finalized by a team of specialists. Subsequently, the dialogue between the dialogic perspective and the ETILS is then used to conduct a qualitative investigation of the analytical-descriptive and analyticalcomparative types. The analysis is conducted by observing the verbal-visual features contained in the translation and comparing the relationships formed in the source text (LP poetry) and the target text (poem in Libras). It is expected that this project will contribute to the inquiry, comprehension, and creation of the translation from LP to Libras, with a focus on the formation of TILS and the inclusion and visibility of deaf community as subjects of poetic-aesthetic practices